2023
DOI: 10.3390/bs13040303
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leader Humor on Employee Creativity during the COVID-19 Period: The Roles of Perceived Workload and Occupational Coping Self-Efficacy

Abstract: Based on the relief theory and similarity attraction theory, this study investigates the influence of leader humor on employee creativity through the mediate impact of employees’ perceived workload, occupational coping self-efficacy, and employee similarity perception with a leader as a potential moderator. The data were collected through an online survey that included matched questionnaire data from 351 employees and their direct leaders in China. This study used SPSS 26 software and Mplus 7.0 software to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Examples of such positive impacts are related to, for instance, blood pressure [37], stress [38], effectiveness [39,40], innovation [41,42], trust [43], burnout, work withdrawal [44], persistent behavior [45], job satisfaction, organizational pride, affective commitment [46], engagement [47], social cohesion [41], creativity communication, enthusiasm, and brightened and more enduring workplace [48]. Humor too seems to be helpful for employees and organizations during the COVID-19 setbacks and aftermaths [49][50][51].…”
Section: Relational Energy and Humormentioning
confidence: 99%
“…Examples of such positive impacts are related to, for instance, blood pressure [37], stress [38], effectiveness [39,40], innovation [41,42], trust [43], burnout, work withdrawal [44], persistent behavior [45], job satisfaction, organizational pride, affective commitment [46], engagement [47], social cohesion [41], creativity communication, enthusiasm, and brightened and more enduring workplace [48]. Humor too seems to be helpful for employees and organizations during the COVID-19 setbacks and aftermaths [49][50][51].…”
Section: Relational Energy and Humormentioning
confidence: 99%
“…Inversely, Amjed and Tirmzi (2016) found a negative relationship of self-defeating humour with employee creativity. Moreover, Hu et al (2023) found that leader humour influenced employee creativity positively. Thus, self-enhancing humour was not only positively related to individual creative performance but also positively related with subordinate creative performance, whereas self-defeating humour was negatively related with employee creativity.…”
Section: Introductionmentioning
confidence: 99%